Distal Humeral Trochlear Geometry Associated With the Spatial Variation of the Dynamic Elbow Flexion Axis - Zou, Diyang; Hu, Xiangjun; An, Kai-Nan; Dai, Kerong; Yu, Xiaowei; Gong, Weihua; Tsai, Tsung-Yuan (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The complexity of the spatial dynamic flexion axis (DFA) of the elbow joint makes the elbow prosthesis design and humeral component alignment challenging. This study aimed to (1) investigate the variation of the spatial DFA during elbow flexion, and (2) investigate the relationship between the distal humeral trochlear geometry and the in-vivo spatial variation of the DFA. Methods: Ten healthy subjects participated in this study. Each subject performed elbow full extension to maximum flexion with hand supination under dual fluoroscopic imaging system (DFIS) surveillance. The 2D fluoroscopic images and the 3D bone models were registered to analyze the in-vivo elbow kinematics and DFAs. The spatial DFA positions were defined as inclination with the medial and lateral epicondyle axis (MLA) in the transverse and coronal planes. The range of DFA positions was also investigated during different flexion phases. The spearman correlation method was used to analyze the relationship between the distal humeral trochlear morphological parameters and the position of DFAs during different flexion phases. Results: The pathway of the DFAs showed an irregular pattern and presented individual features. Medial trochlear depth (MTD) (r=0.68, p=0.03) was positively correlated with the range of DFA position (2.8°±1.9°) in the coronal plane from full extension to 30° of flexion. Lateral trochlear height (LTH) (r=-0.64, p=0.04) was negatively correlated with DFA position (-1.4°±3.3°) in the transverse plane from 30° to 60° of flexion. A significant correlation was found between LTH with DFA position in coronal (r=-0.77, p=0.01) and transverse plane (r=-0.76, p=0.01) from 60° to 90° of flexion. Conclusion: This study showed that the pathway of the dynamic flexion axis has an individual pattern. The medial and lateral trochlear size were the key parameters that might affect the elbow joint flexion function. When recovering complex distal humeral fractures or considering implant design of total elbow arthroplasty, surgeons should pay more attention to the medial and lateral trochlea's geometry, which may help restore normal elbow kinematics.